2022
DOI: 10.1002/pssa.202200089
|View full text |Cite
|
Sign up to set email alerts
|

1,8‐Octanedithiol as an Effective Intermediate Layer for Deposition of Cu Electrodes via Inkjet Printing and Laser Sintering on III–V Triple‐Junction Solar Cells

Abstract: This research study combines surface modification techniques with back‐end‐of‐line (BEOL) methods for cost‐effective, scalable front contact electrode deposition on III–V solar cells. Copper nanoparticle grids are deposited by inkjet printing on surface‐modified III–V solar cells. The deposition of a self‐assembled monolayer (such as 1,8‐octanedithiol) as an intermediate layer is a proven method for surface modification to improve the wettability of the substrate surface and the adhesion of the printed copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…address these limitations, significant research has been done on developing alternative front side metallization schemes, aiming at narrow fingers, high aspect ratios, low-cost abundant material, low-temperature process, and low contact resistance interfaces with c-Si surfaces. Few research groups have developed less-silver or silver-less approaches based on Ni/Cu, Ni/Ag, [18] Ti/Pd/Ag, [19] Al/Ag, [20] Pd/Ag, [21] Cu NP ink [22] Ni/Cu/Ag, [23] and Ni/Cu/Sn [7,23,24] metallization for solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…address these limitations, significant research has been done on developing alternative front side metallization schemes, aiming at narrow fingers, high aspect ratios, low-cost abundant material, low-temperature process, and low contact resistance interfaces with c-Si surfaces. Few research groups have developed less-silver or silver-less approaches based on Ni/Cu, Ni/Ag, [18] Ti/Pd/Ag, [19] Al/Ag, [20] Pd/Ag, [21] Cu NP ink [22] Ni/Cu/Ag, [23] and Ni/Cu/Sn [7,23,24] metallization for solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…After epitaxy, one of the major costs during the fabrication of III-V solar cells is the front contact metallization [2]. Several variations of the metallization and/or metal deposition technique have been studied in order to reduce this cost [6][7][8][9]. In particular, it was shown that the standard AuGe/Ni/Au front ohmic contact metallization could be replaced by a thin Pd/Ge/Ti/Pd stack combined with a thick Al layer [9].…”
Section: Introductionmentioning
confidence: 99%
“…Other research groups work on seed and plate metallization of III-V solar cells utilizing copper-based seeds. So far, they do not approach the efficiency of reference cells with photolithographically structured evaporated metal contacts 15 .…”
mentioning
confidence: 99%